2023
DOI: 10.1371/journal.pone.0286494
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the association between mental health and people’s perceived and actual ability to practice hygiene-related behaviours in humanitarian and pandemic crises: A scoping review

Emily Yasmin Ghassemi,
Astrid Hasund Thorseth,
Karine Le Roch
et al.

Abstract: Humanitarian crises such as disease outbreaks, conflict and displacement and natural disasters affect millions of people primarily in low- and middle-income countries. Here, they often reside in areas with poor environmental health conditions leading to an increased burden of infectious diseases such as gastrointestinal and respiratory infections. Water, sanitation, and hygiene behaviours are critical to prevent such infections and deaths. A scoping review was conducted to map out what is known about the assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…A stark finding of this evaluation was that the protracted nature of the water and food security crisis in Zimbabwe was not viewed as a ‘crisis’ by frontline staff, nor did they view chronic diarrhoea challenges in the region as being a critical disease risk necessitating the prioritisation of handwashing behaviour change initiatives. Other research has identified that handwashing is often not ‘problematised’ by populations during crises, nor is it prioritised by humanitarians for a variety of reasons [ 14 , 61 ]. However, these variations in understanding have caused the global-level Wash’Em trainers to rethink the way fragility, crises, and outbreaks are described and has prompted the team to reflect on how Wash’Em can be used to support resilience building and crisis mitigation programming.…”
Section: Discussionmentioning
confidence: 99%
“…A stark finding of this evaluation was that the protracted nature of the water and food security crisis in Zimbabwe was not viewed as a ‘crisis’ by frontline staff, nor did they view chronic diarrhoea challenges in the region as being a critical disease risk necessitating the prioritisation of handwashing behaviour change initiatives. Other research has identified that handwashing is often not ‘problematised’ by populations during crises, nor is it prioritised by humanitarians for a variety of reasons [ 14 , 61 ]. However, these variations in understanding have caused the global-level Wash’Em trainers to rethink the way fragility, crises, and outbreaks are described and has prompted the team to reflect on how Wash’Em can be used to support resilience building and crisis mitigation programming.…”
Section: Discussionmentioning
confidence: 99%